New Caribbean deal : the next five years - Burgaud, Jean-Marie (Economist Publications LondonGB, 1986)
Provides economic panorama of the Caribbean, focusing on the CBI beneficiaries and Puerto Rico. Discusses the challenges facing the Caribbean area, its economic changes, and provides a system for checking the feasibility of a CBI investment strategy. Gives five year perspective of the business climate and opportunities of 7 major Caribbean countries. Also provides information, in brief, of the other eight CBI beneficiaries.